The Little Green Data Book 2015 - World Bank (Washington, DC, 2015)
The Little Green Data Book 2015 is a pocket-sized ready reference on key environmental data for over 200 countries. Key indicators are organized under the headings of agriculture, forestry, biodiversity, oceans, energy, emission and pollution, and water and sanitation. For the third year, The Little Green Data Book presents a new set of ocean-related indicators, highlighting the role of oceans in economic development.